Linking the geochemistry of crude oils and petroleum inclusions in the Ubarana and Lorena oilfields, Potiguar Basin, Brazilian Equatorial Margin. (October 2018) - Pestilho, André Luiz Silva; Monteiro, Lena Virgínia Soares; Carbonezi, Carlos Alberto; Jorge, Sandra Brandão; Santos Neto, Eugênio V.
Highlights: A homogeneous composition of oil was trapped in the Açu Formation fluid inclusions. Varied oil compositions in inclusions from the Pendência and Ponta do Mel formations. Lorena Oilfield was sourced by the lacustrine sequences of the Umbuzeiro graben. Açu inclusion oil correlates with the mixed oils from the Alagamar Formation. Ponta do Mel inclusion oil correlates with lacustrine facies of Alagamar Formation. Abstract: A study of petroleum inclusions based on ultraviolet fluorescence petrography, microspectrophotometry and biomarker analyses was carried out on samples from two wells of the onshore Lorena and the offshore Ubarana oilfields, Potiguar Basin, Brazil. This study aimed to evaluate the contribution and compositional variability of oils associated with different source rocks through the geochemical correlation of petroleum inclusions and crude oils. Three groups of inclusions were identified: (i) a group from the Lorena reservoir (Pendência Formation); (ii) a second from the Ubarana siliciclastic reservoir (Açu Formation); and (iii) a third from the carbonates adjacent to the Ubarana reservoir (Ponta do Mel Formation, PML). Fluorescence microspectrophotometry shows that the three groups of inclusions have different API gravity oils, variable proportion of saturate, aromatic, resins and asphaltenes and are not biodegraded. Moreover, Pendência and PML inclusions suggest multiple pulses of hydrocarbon migration, while Açu inclusions record a homogeneous pulse. Biomarkers indicate that the Pendência and Açu inclusion oils correlate with reservoir oil extracts. The Pendência inclusion oils are similar to the lacustrine oils of the Umbuzeiro graben (Pendência Formation), whereas the Açu inclusion oil displays closer biomarker signature to the Areia Branca trend of mixed oils (Alagamar Formation source rock). However, the oil from fluid inclusions of the PML has characteristics of the Alagamar Formation lacustrine organic facies. The absence of mixed oils in the PML suggests an earlier lacustrine oil migration through the carbonate fractures prior to the main infill of mixed oils in the Ubarana oilfield.